MOBILE-ADAPTABLE CLOUD-BASED EDUCATION MANAGEMENT INFORMATION SYSTEMS: LESSONS FROM OGUN STATE'S DIGITAL PLATFORM FOR EDUCATION REVITALIZATION (DIPER) (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines the implementation and impact of Ogun State's Digital Platform for Education Revitalisation (DiPER), an innovative mobile-optimized, cloud-based Education Management Information System (EMIS) in Nigeria. Through a mixed-methods research approach incorporating system analytics (n=18,327 users), stakeholder surveys (n=4,215), and comparative case analysis, we demonstrate how DiPER's unique architecture addresses critical infrastructure challenges while achieving remarkable adoption rates of 86.4% among educators. Key findings reveal that mobile devices account for 81.3% of system access, cloud hosting ensures 99.2% uptime despite persistent power fluctuations, and automated reporting features reduce administrative workload by 47.6%. The study contributes an evidence-based framework for implementing mobile-cloud EMIS in resource-constrained environments, offering seven validated implementation principles that balance technological innovation with contextual realities. Our analysis provides valuable insights for policymakers and education administrators seeking to leverage digital technologies to transform education management systems in developing contexts.
Keywords: mobile-optimized EMIS; cloud computing; education management; digital transformation; Nigeria; developing contexts